Bladder Pain Syndrome With Repeated Bladder Hydrodistention—A Case of Functional Somatic Syndrome Considered in Relation to Alexithymia - Naoki Wada; Tsubasa Hatakeyama; Taichiro Ishimaru; Ryoken Tsunekawa; Kotona Miyauchi; Daiki Kikuchi; Takeya Kitta; Masaki Watanabe (IJU Case Reports)
ABSTRACT Introduction We present a patient with bladder pain syndrome (BPS) who underwent repeated bladder hydrodistentions. Case Presentation A female patient visited our department because of refractory bladder pain. She was diagnosed with BPS; she had only mucosal bleeding after distention. Her bladder pain improved after hydrodistention; however, the symptoms flared up within a few months. She also consulted with the palliative care department and was diagnosed with chronic pain associated with alexithymia. Various drugs were administered; however, none were effective or continued because of side effects. It was also challenging for her to embrace introspective counseling. Ultimately, along with her strong desire, the hydrodistention continued every few months. Her bladder capacity was approximately 200 mL. Conclusion BPS with uncontrolled bladder pain may be a functional somatic syndrome associated with alexithymia, and interventions such as psychosomatic medicine could be necessary from the early stage.